ОГРАНИЧЕНИЯ ИСПОЛЬЗОВАНИЯ ПРОТОКОЛА ЗАЩИТЫ ТРАНСПОРТНОГО УРОВНЯ SSL ДЛЯ ОБЕСПЕЧЕНИЯ БЕЗОПАСНОСТИ ВЗАИМОДЕЙСТВИЯ WEB-СЕРВИСОВ - Денис Александрович Хафизов (Безопасность информационных технологий, 2009)
The model ensuring secured connection between components at transport level in the distributed service environment is examined, its short description is provided. The conclusion on the need for the coordinated selection and application of technologies for the purpose of organizing information infrastructure of services and ensuring its safety is substantiated.